Regional conflicts as an attribute of global instability - Baturin, V.S.; Esim, G.; Shakirov, S.E. (Journal of security and sustainability issues, 2019)
The article presents the nature of regional conflicts as one of the types of social conflicts in the context of traditional (naturalistic) and activity approaches. The authors reveal a number of conditions that determined the reasons for use of social conflicts in the second half of the 20th century, as well as the features of the increased demand for them in terms of solving the problems generated by contemporary globalization processes. Particular attention is paid to the threat posed by the attempts of a number of countries to use regional conflicts in order to demonstrate their power to the rest of the world. The article presents the analysis of the reasons contributing to the transformation of regional conflicts into an attribute of global instability, as well as considers the prospects of the formation of a multipolar world arrangement model, where the very possibility of regional conflicts could be minimized.
Keywords: regional conflict; the activity approach; conflictogenity; the conflict escalation; counteractivity; the subject-object paradigm; destabilization; uncontrollable chaos